Normative data of liver size in Kashmiri adult population using ultra-sonography, India - Gul, Snobar; Itoo, Mohammad Saleem; Nisa, Gousia (International Journal of Research in Medical Sciences, 2019)
Background: A number of disorders are accompanied by altered size of various abdominal organs like liver including infective, infestation, infiltrative, immunological and malignant conditions. Medical imaging has played an important role in helping physicians for taking normal anatomical dimensions and establishing diagnosis. This study was carried out to determine the normal standards of liver size and its relationship with body weight, height and body mass index. Methods: A cross sectional study was done in GMC Srinagar, Jammu and Kashmir, India for a period of 18 months. 300 staff members in the age group of 19 to 55 years took part in this study. Results: The mean craniocaudal length of liver was 13.08±1.04cms. Authors found a significant correlation of liver size with body weight and body mass index. Conclusions: Body weight and BMI are important determining factors for liver size. Nomograms from this study can be beneficial for diagnosing pathological enlargement or reduction of liver in Kashmiri ethnic population.